Fundamentals of commercial loan documentation - Behrens, Robert H.; Evans, James W. (Illinois : Bank Administration Institute, 1989)
The purpose of this book is to provide the banker with a thorough working knowledge of the fundamentals of commercial loan documentation
Includes index
osc 31/10/17
Loans
Keywords: Bank Administartion; Loan - bank services